The wedding girl - Wickham, Madeleine, 1969. (London : Transworld Publishers, 2010)
Having rashly agreed ten years earlier to a marriage of convenience with her gay friend's partner to secure his citizenship, Milly hides the truth about her married status from her wealthy and serious fiancé until four days before her wedding.
Keywords: Weddings -- Planning -- Fiction; Impediments to marriage -- Fiction